2022
DOI: 10.3389/fmicb.2022.1009364
|View full text |Cite
|
Sign up to set email alerts
|

Fire blight resistance, irrigation and conducive wet weather improve Erwinia amylovora winter survival in cankers

Abstract: Erwinia amylovora causes fire blight, a disease responsible for enormous economic losses in the pome fruit-producing areas where it is present. Despite the abundant research on fire blight, information about E. amylovora population dynamics and survival in fire blight cankers and the plant defense responses to this pathogen in the infected bark are limited. In our study, we obtained fire blight cankers in apple, pear, and Asian pear cultivars showing differing resistance to the disease by shoot inoculation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…In fall 2017, the concentration of E. amylovora in rootstocks might have declined below the limit of detection of PCR (EPPO, 2013;Ham et al, 2022). The 10.1% -28.5% higher rootstock canker incidence in fall 2017, in comparison to the precent of E. amylovora detections with PCR in fall 2016, aligns well with the faster death of susceptible host wood from cankers and lower linked incidence of E. amylovora-positive cankers on their branches (Santander et al, 2022b). Viability digital PCR this work showed that more E. amylovora cells die in cankers on highly susceptible pome fruit tree hosts due to large extent of damage on branches and faster tissue death, thus causing lower detection rates of E. amylovora-positive cankers.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In fall 2017, the concentration of E. amylovora in rootstocks might have declined below the limit of detection of PCR (EPPO, 2013;Ham et al, 2022). The 10.1% -28.5% higher rootstock canker incidence in fall 2017, in comparison to the precent of E. amylovora detections with PCR in fall 2016, aligns well with the faster death of susceptible host wood from cankers and lower linked incidence of E. amylovora-positive cankers on their branches (Santander et al, 2022b). Viability digital PCR this work showed that more E. amylovora cells die in cankers on highly susceptible pome fruit tree hosts due to large extent of damage on branches and faster tissue death, thus causing lower detection rates of E. amylovora-positive cankers.…”
Section: Discussionmentioning
confidence: 52%
“…The life cycle of fire blight pathogen, Erwinia amylovora (Burrill; Winslow et al, 1920) starts by survival in apple wood bark around fire blight canker edges and below the visible canker necrosis (Santander et al, 2019, Santander et al, 2022b. In spring, E. amylovora emerges on the surface of cankers and can be disseminated by insects, rain, or wind to flowers and shoots.…”
Section: Introductionmentioning
confidence: 99%
“…When fire blight cankers develop on the trunks, limbs, and rootstock, they can girdle the stem and kill branches, treetop, or whole mature or young trees in highdensity pear orchards. Pear trees are much more susceptible to fire blight in comparison to apple trees (Santander et al, 2022a). Canker damage is much worse on young tree tissues of juvenile trees and cankers can serve as inoculum sources for future infections on mature trees.…”
Section: Discussionmentioning
confidence: 99%
“…After E. amylovora invades wood tissues from infected flowers and shoots, new fire blight cankers develop on wood, thus repeating the life cycle (Acímovićet al, 2014a, Acímovićet al, 2019a. However, even though cankers have great importance in disease epidemiology, understanding the parts of E. amylovora life cycle on shoots and in fire blight cankers is still limited (Santander et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation